Understanding the Interaction of Polyelectrolyte Architectures with Proteins and Biosystems. Issue 8 (27th October 2020) - Achazi, Katharina; Haag, Rainer; Ballauff, Matthias; Dernedde, Jens; Kizhakkedathu, Jayachandran N.; Maysinger, Dusica; Multhaup, Gerd
Abstract: The counterions neutralizing the charges on polyelectrolytes such as DNA or heparin may dissociate in water and greatly influence the interaction of such polyelectrolytes with biomolecules, particularly proteins. In this Review we give an overview of studies on the interaction of proteins with polyelectrolytes and how this knowledge can be used for medical applications. Counterion release was identified as the main driving force for the binding of proteins to polyelectrolytes: Patches of positive charge become multivalent counterions of the polyelectrolyte and lead to the release of counterions from the polyelectrolyte and a concomitant increase in entropy. This is shown from investigations on the interaction of proteins with natural and synthetic polyelectrolytes. Special emphasis is paid to sulfated dendritic polyglycerols (dPGS). The Review demonstrates that we are moving to a better understanding of charge–charge interactions in systems of biological relevance. Research along these lines will aid and promote the design of synthetic polyelectrolytes for medical applications. Abstract : Polyelectrolytes such as DNA or heparin are long linear or branched macromolecules onto which charges are appended. The counterions neutralizing these charges can dissociate in water and this will largely determine the interaction of such polyelectrolytes with biomolecules, particularly with proteins. This Review discusses studies on the interaction of proteins with polyelectrolytes and how this knowledge can be used for medical applications.